2016
DOI: 10.7554/elife.14972
|View full text |Cite
|
Sign up to set email alerts
|

Decreased motor cortex excitability mirrors own hand disembodiment during the rubber hand illusion

Abstract: During the rubber hand illusion (RHI), subjects experience an artificial hand as part of their own body, while the real hand is subject to a sort of 'disembodiment'. Can this altered belief about the body also affect physiological mechanisms involved in body-ownership, such as motor control? Here we ask whether the excitability of the motor pathways to the real (disembodied) hand are affected by the illusion. Our results show that the amplitude of the motor-evoked potentials recorded from the real hand is sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
125
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(150 citation statements)
references
References 40 publications
11
125
13
1
Order By: Relevance
“…and our results may be due to the different cognitive mechanisms engaged during the experience of rubber and virtual hand illusion respectively. Indeed, previous findings suggest that the illusory ownership over the rubber hand comes with a disownership of the real one that brings about a decrease in skin temperature (Moseley et al ., ; Kammers et al ., ) and a modulation of tactile processing (Moseley et al ., ), pain thresholds (Hänsel et al ., ), histamine reactivity (Barnsley et al ., ) and MEP amplitude (Della Gatta et al ., ). However, in IVR, the virtual and real bodies are unified in one overall body representation that brings about a ‘replacement’ of the real body rather than disownership feelings (Llobera et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…and our results may be due to the different cognitive mechanisms engaged during the experience of rubber and virtual hand illusion respectively. Indeed, previous findings suggest that the illusory ownership over the rubber hand comes with a disownership of the real one that brings about a decrease in skin temperature (Moseley et al ., ; Kammers et al ., ) and a modulation of tactile processing (Moseley et al ., ), pain thresholds (Hänsel et al ., ), histamine reactivity (Barnsley et al ., ) and MEP amplitude (Della Gatta et al ., ). However, in IVR, the virtual and real bodies are unified in one overall body representation that brings about a ‘replacement’ of the real body rather than disownership feelings (Llobera et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Several pieces of evidence showed that the sense of position and motion rely on the integration of visual and proprioceptive information, with vision usually dominating proprioception (van Beers et al 1999;Holmes & Spence, 2005). This integration seems to be dependent on the level of congruency between the two afferent sets of information as suggested either by studies on the rubber hand illusion in healthy subjects (Makin et al 2008;della Gatta et al 2016;Burin et al 2017) or by studies on the pathological embodiment in brain-damaged patients (Fossataro et al 2016(Fossataro et al , 2018. Also, a behavioural study using the mirror box paradigm revealed that illusion experienced in conditions of multimodal stimulation was larger than those reported in unimodal conditions (Guerraz et al 2012).…”
Section: Discussionmentioning
confidence: 98%
“…; della Gatta et al . ; Burin et al . ) or by studies on the pathological embodiment in brain‐damaged patients (Fossataro et al .…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the three senses of embodiment are not independent from each other. For example, brain studies and movement disorders seem to show that there is a mutual relationship between affective embodiment and the motor system (Schütz-Bosbach et al, 2006;Della Gatta et al, 2016;Burin et al, 2017;Fossataro et al, 2018). Affective embodiment requires multisensory integration within a fronto-parietal network.…”
Section: Affective Motor and Spatial Embodimentmentioning
confidence: 99%
“…Also, the effects of somatosensory inputs to the real hand are reduced, leading to a lower intensity sensation (Folegatti et al, 2009;Zopf et al, 2011b;Kilteni and Ehrsson, 2017). Further, TMS elicited motor evoked potentials are reduced, suggesting the motor system is less activated toward the real hand's muscles (Della Gatta et al, 2016). Threatening the fake hand also elicits strong cortical startle responses (Ehrsson et al, 2007;Gentile et al, 2013).…”
Section: The Rubber Hand Illusionmentioning
confidence: 99%